The God of the groups - McIntosh, Chad A. (Religious studies, 2016)
I argue that Social Trinitarians can and should conceive of God as a group person. They can by drawing on recent theories of group agency realism that show how groups can be not just agents but persons distinct from their members - albeit, I argue, persons of a different kind. They should because the resultant novel view of the Trinity - that God is three intrinsicist' persons in one functional' person - is theologically sound, effectively counters the most trenchant criticisms of Social Trinitarianism, and enjoys independent theological support from the biblical notion of corporate personality'.